ABUNDANCE OF TREES USED AS FOOD BY PRIMATES IN FRAGMENTS OF ATLANTIC FOREST - Valdecir da Silva (Environmental Smoke, 2018)
Forest fragmentation favours the propagation of some arboreal primate species that can alter the floristic composition of a community. This process may be associated with the loss of seed dispersants. In this work we propose to identify if the presence of frugivorous primates of medium and large size (Sapajus flavius and Alouatta belzebul) can influence forest diversity and structure. Further, we ask if the size of the fragment affects the availability of resources for these primates. Three fragments were studied in the Atlantic Forest of the State of Paraíba, Brazil, located in the municipalities of Sapé, Mamanguape, Rio Tinto, and Mataraca. In each area 25 plots of 50 x 4 m were delimited, randomly distributed along trails and transects. All trees with chest-high circumferences (CAP) above 12 cm found within the plots were marked with ribbons, and numbered continuously. A total of 114 plant species were documented in the Pacatuba Forest, 79 in the Asplan Forest, and 97 in the “Guaribas” (Sema III) Biological Reserve (REBIO) Forest. According to the Chao and Jacknife estimators, the REBIO Guaribas Forest can present more species than recorded in the present investigation. Species Tapirira guianensis, Protium giganteum and Protium heptaphyllum are the most abundant in the Asplan, Pacatuba and Sema III Forests, respectively. In the REBIO Guaribas Forest, the Shannon diversity index was (H') = 3.75, the Alpha-Fisher index was = 26.57 and the Simpson index (1-D) was = 0.90. Pacatuba was the forest fragment with the highest index of diversity (H') = 375, Alpha-Fischer = 33.74 and Simpson (1-D) = 0.95. Pacatuba and REBIO Guaribas Forsts possess greater Beta diversity. The results suggest that local and historical factors possibly increase Beta diversity, contributing to the increase in resources used as food by primates. Therefore, the presence of primates of medium and large size in the Pacatuba Forest may affect the diversity of resources, contributing to the dispersion of large fruits and seeds. The presence of primates of medium and large size can thus contribute to the preservation of floristic diversity in forest fragments.